Novel design of multiplexers using adiabatic logic - Purna Ramesh, Addanki (International Journal of Engineering and Technology, 2019)
Multiplexer (or Mux) is a digital circuit that selects one of several analog or digital input signals and forwards the selected input into a single line. A multiplexer is also called a data selector. Multiplexers implemented in different ways. Adiabatic logic dissipates less energy loss because of thermodynamic process, in which there is no energy exchange. Adiabatic logic works with the concept of switching activities which reduces the power by giving stored energy back to the supply. These circuits are low power circuits which use reversible logic to conserve energy. In this paper three multiplexer designs are implemented using CMOS logic and two adiabatic logic methods i.e., Efficient Charge Recovery Logic (ECRL) and Clocked Adiabatic Logic (CAL). These circuits are designed, simulated and synthesized using Mentor Graphics tool. The result shows that CAL design consumes less power compared with ECRL and CMOS logic.Â Â Â